Community Radio at the Beginning of the 21st Century: Commercialism vs. Community Power - Dunaway, David (Javnost-The Public, 1998)
This article charts the historical development of community radio in the United States, and makes comparisons with the development of stations in Europe. Parallels are noted and illustrated from both the author’s personal experience and academic analysis. Two typologies are proposed for understanding this development in which key aspects of stations are used for comparing stations in the mid-1970s to those in the late 1990s. The article ends with formulation of a number of issues which should be placed high on the research agenda, and a plea for consideration of the US model of listener-sponsorship as a viable “third way” for community radio initiatives in the 21st century.